2015
DOI: 10.1016/j.contraception.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Risk of uterine perforation with levonorgestrel-releasing and copper intrauterine devices in the European Active Surveillance Study on Intrauterine Devices

Abstract: The European Active Surveillance Study on Intrauterine Devices is the first large-scale, prospective, non-interventional study to compare the perforation risk in LNG-IUS and copper IUD users. It is the first to examine the independent roles that breastfeeding status and postpartum status have on perforation risk. Conducted during routine clinical practice, the findings are generalizable to broader populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
140
1
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(163 citation statements)
references
References 16 publications
(24 reference statements)
7
140
1
15
Order By: Relevance
“…Breastfeeding and proximity to a recent delivery (up to 36 weeks) were both independently associated with an increased risk of uterine perforation.1 In addition to timing of the insertion, history of caesarean delivery, the skill and experience of performing physician and position of uterus or presence of a uterine anomaly are reported risk factors of uterine perforation. [1][2][3]5,6 It is not well known whether this complication occur secondary to a technical error or was related to the patient's own conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breastfeeding and proximity to a recent delivery (up to 36 weeks) were both independently associated with an increased risk of uterine perforation.1 In addition to timing of the insertion, history of caesarean delivery, the skill and experience of performing physician and position of uterus or presence of a uterine anomaly are reported risk factors of uterine perforation. [1][2][3]5,6 It is not well known whether this complication occur secondary to a technical error or was related to the patient's own conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Perforation of the uterus by an IUD is rare with a reported incidence of 0.2-3.6 per 1000 insertions. [1][2][3] This not only, increases the risk of contraceptive failure, but also puts the patient at probable further complications. Migration into the peritoneal cavity can causes serious complications such as adhesion-fistula formation, infection, abscess and perforation into bowel, bladder or blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for uterine perforation are postpartum amenorrhea, breastfeeding, postpartum period less than 6 months, and inexperienced practitioners [3,4]. Symptoms of IUD misplacement are abnormal vaginal bleeding and abdominal pain; however, at times, this complication may be asymptomatic [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Rare complications of IUD insertion are embedment in the myometrium and perforation beyond the uterine serosa, with an incidence rate of 0.01% [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The large ongoing international prospective EURAS-IUD study (European Active Surveillance Study for Intrauterine Devices) revealed perforation rates of 0.68/1000 insertions for the LNG-IUS and 0.41/1000 insertions for Cu-IUCDs at 1 year of follow up (Heinmann 2015). 1 The risk factor for uterine perforation by IUCD is type of IUCD, position and size of uterus, congenital anomalies, infection, history of abortion and insertion in postpartum period.…”
Section: Introductionmentioning
confidence: 99%